Kriteria Fī Sabīlillāh sebagai Mustahik Zakat pada Lembaga Amil Zakat Nasional Wahdah Islamiyah Pusat - Khaerul Aqbar; Nuraeni Novira; Muhammad Muhammad; Musfirah Az-Zahrah A. (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2022)
This study aims to determine and understand the criteria of fῑ sabῑlillāh as zakat mustahik at the National Amil Zakat Institution (Laznas) of Centre of Wahdah Islamiyah. The study use a qualitative type of field research using a normative approach. The research results found are as follows; (1) Fῑ Sabῑlillāh is one of the eight groups who are entitled to receive zakat. The definition of fῑ sabῑlillāh itself is a deed that leads to the pleasure of Allah swt. and His heaven, especially jihad to elevate the sentence of monotheism. At present, there are more categories of fῑ sabῑlillāh, such as the construction of mosques, hospitals, schools, orphanages, orphans and other da'wah facilities. (2) The criteria for fȋ sabȋlillāh as zakat mustahik at Laznas Wahdah Islamiyah as also used as a reference by the National Amil Zakat Agency (BAZNAS), that fȋ sabȋlillāh are all activities that support da'wah activities, both da'wah implementers (da'i), da'wah institutions and facilities infrastructure that supports the da'wah itself. The determination of mustahik anāf fȋ sabȋlillāh is carried out after going through several stages of the survey of mustahik candidates. The data obtained from the survey is then processed whether the prospective mustahik deserves to receive zakat or not, the next is sorting the program according to the needs of the mustahik. (3) The distribution of zakat fȋ sabȋlillāh at Laznas Wahdah Islamiyah is carried out after the mustahik selection process using the survey method. Laznas Wahdah Islamiyah's strategy in distributing zakat is to see which asnaf is a priority and is encountered in its management. The distribution of funds is carried out directly by Laznas Wahdah Islamiyah.